The Role of Diet, Eating Behavior, and Nutrition Intervention in Seasonal Affective Disorder: A Systematic Review - Yang, Yongde; Zhang, Sheng; Zhang, Xianping; Xu, Yongjun; Cheng, Junrui; Yang, Xue (Frontiers in Psychology, 2020)
Background: Seasonal affective disorders (SAD) is a biologic and mood disorder with a seasonal pattern. Dietary intervention and nutritional status have been reported to affect SAD development. The objective of this study was to systematically review the evidence of associations between diet, eating behavior, and nutrition intervention with SAD. Methods: We performed a comprehensive search of the MEDLINE, EMBASE, Web of Science and Google Scholar from inception up to the first of July, 2019. Studies of diet, eating behavior, and nutrition intervention, and associations with SAD were included. Two independent investigators extracted data based on study designs, participants, outcomes, exposures, and association measures. Results: Eleven studies were included: six studies revealed the distinctive pattern of diet and eating behavior of SAD patients, while five studies explored the efficacy of nutrition intervention on SAD. Vegetarianism and alcoholism were associated with higher SAD prevalence, but normal alcohol intake was not correlated with SAD severity. Compare with non-clinical subjects, SAD patients tended to consume significantly more dinners and evening snacks during weekdays and weekends, exhibited a higher frequency of binge eating, external eating, and emotional eating. Additionally, they presented cravings for starch-rich food and food with high fiber. However, ingestion of carbohydrate-loaded meals did not mitigate SAD symptoms, neither did the supplementation of Vitamin D and Vitamin B12 show therapeutic effects against SAD. Conclusion: Studies suggest that SAD patients may exhibit distinctive diet preference and eating behaviors, but currently no nutrition intervention was proved to be effective in ameliorating SAD symptoms. Further evidence is needed from RCTs with larger sample size and longer duration.